1987
DOI: 10.1111/j.1476-5381.1987.tb11310.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacology of endothelium‐derived relaxing factor, nitric oxide and prostacyclin in platelets

Abstract: The pharmacological effects of endothelium‐derived relaxing factor (EDRF), nitric oxide (NO) and prostacyclin on human and rabbit platelets were examined. EDRF is released from porcine aortic endothelial cells, cultured on microcarriers and treated with indomethacin, in sufficient quantities to inhibit platelet aggregation induced by 9,11‐dideoxy‐9α,11α‐methano epoxy‐prostaglandin F2α (U46619) and collagen. The anti‐aggregating activity of EDRF was potentiated by M&B 22948, a selective inhibitor of cyclic GMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
296
1
19

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 785 publications
(328 citation statements)
references
References 23 publications
(31 reference statements)
12
296
1
19
Order By: Relevance
“…6). The potency of CNP was akin to that reported for NO released by isolated vascular endothelial cells (23,24) and fits with the reported ability of CNP to block thrombus formation (25).…”
Section: Cnp Inhibits Platelet-leukocyte Aggregate Formation and Platsupporting
confidence: 65%
See 1 more Smart Citation
“…6). The potency of CNP was akin to that reported for NO released by isolated vascular endothelial cells (23,24) and fits with the reported ability of CNP to block thrombus formation (25).…”
Section: Cnp Inhibits Platelet-leukocyte Aggregate Formation and Platsupporting
confidence: 65%
“…CNP (0.1-1 M) was superfused for 10 min, and leukocyte flux was recorded. To investigate the involvement of the NPR-C in responses to CNP, the ability of the selective NPR-C agonist (17), cANF [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] (1 M) to inhibit leukocyte rolling was also explored.…”
Section: Assessment Of the Effect Of Cnp On Basal Leukocyte Activatiomentioning
confidence: 99%
“…Since EDRF has been now characterized both biologically and chemically in a variety of systems as NO Hutchinson et al, 1987;Radomski et al, 1987;Ignarro et al, 1987, Khan & Furchgott, 1987Moncada et al, 1988;Kelm et al, 1988), whose synthesis can be inhibited by L-NMMA (Palmer et al, 1988b;Rees et al, 1989a,b) the current findings with L-NMMA in the rat further implicate endothelium-derived NO in the regulation of cardiovascular tone and blood pressure, and as a mediator of the hypotensive actions of endogenous endothelium-dependent vasodilators in vivo. The modulation of local substrate levels and enzymic activity involved with the biosynthesis of NO in the vascular endothelium may, therefore, make an important contribution to the physiological regulation and pathological conditions of the cardiovascular system.…”
Section: Discussionmentioning
confidence: 80%
“…It has been demonstrated that NO is destroyed by superoxide anions and that inactivation of superoxide anions protects and prolongs the action of NO Moncada et al, 1986;Rubanyi & Vanhoutte, 1986). Thus, superoxide dismutase induces relaxation of rat aortic strips with intact endothelium (Rubanyi & Vanhoutte, 1986;Rimele et al, 1988) and increases the antiaggregatory activity of neutrophils (Radomski et al, 1987). Compounds with steroidal structures were recently shown to be potent O-scavengers and to be active in protecting neurones against peroxide injury (Hall et al, 1987).…”
Section: Resultsmentioning
confidence: 99%